2020
DOI: 10.31933/dijdbm.v1i6.573
|View full text |Cite
|
Sign up to set email alerts
|

Happiness at Work and Organizational Citizenship Behavior in Krakatau Steel

Abstract: Every company must be able to invite its employees to provide a model of employee happiness at work and appropriate organizational citizenship behavior in accordance with the needs of the company which can make a person's organizational citizenship behavior better. This study aims to determine the model of employee happiness at work and organizational citizenship behavior of an employee in a company. This research is a descriptive and verification research using simple linear regression analysis, where the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
1
0
3
Order By: Relevance
“…Salas-Vallina et al (2016) investigated the mediation impact of organisational learning capability on the link between employee happiness and organisational citizenship behaviour and found that organisational learning capability has a strong impact on the relationship. Similar studies established a positive linkage between employee happiness and organisational citizenship behaviours (Agustina et al, 2020, Palihakkara & Weerakkody, 2019. In addition, Mohammad et al ( 2011) measured how two dimensions of organisational citizenship behaviours (OCB for individuals and OCB for organisations) are associated with both internal and external forms of contentment.…”
Section: The Connection Between Employee Happiness (Ehap) and Ocbmentioning
confidence: 67%
“…Salas-Vallina et al (2016) investigated the mediation impact of organisational learning capability on the link between employee happiness and organisational citizenship behaviour and found that organisational learning capability has a strong impact on the relationship. Similar studies established a positive linkage between employee happiness and organisational citizenship behaviours (Agustina et al, 2020, Palihakkara & Weerakkody, 2019. In addition, Mohammad et al ( 2011) measured how two dimensions of organisational citizenship behaviours (OCB for individuals and OCB for organisations) are associated with both internal and external forms of contentment.…”
Section: The Connection Between Employee Happiness (Ehap) and Ocbmentioning
confidence: 67%
“…Konsep kebahagiaan di tempat kerja pertama kali diperkenalkan oleh Hans Selye pada tahun 1936. Kebahagiaan didefinisikan sebagai "kekuatan atau tekanan yang diberikan pada objek atau orang untuk melawannya, kekuatan dan upaya untuk mempertahankan kondisi aslinya (G. Agustina et al, 2020).…”
Section: Pendahuluanunclassified
“…Psikologi positif didefinisikan sebagai "ilmu pengalaman subjektif positif, sifat individu positif, dan institusi positif." (Agustina et al, 2020) Kerangka Penelitian…”
Section: Kebahagiaan DI Tempat Kerjaunclassified
See 1 more Smart Citation